Endoscopic ultrasound‐guided portal pressure gradient with liver biopsy: 6 years of endo‐hepatology in practice. Issue 7 (20th May 2022) - Choi, Alyssa Y.; Kolb, Jennifer; Shah, Sagar; Chahine, Anastasia; Hashimoto, Rintaro; Patel, Anish; Tsujino, Takeshi; Huang, Jason; Hu, Ke‐Qin; Chang, Kenneth; Samarasena, Jason B.
Abstract: Background and Aim: The portal pressure gradient (PPG) is a useful predictor of portal hypertension (PH) related complications. We previously showed the feasibility and safety of endoscopic ultrasound guided PPG measurement (EUS‐PPG). Now EUS‐guided liver biopsy (EUS‐bx) has been shown to be a safe and effective alternative to percutaneous or Interventional Radiology‐guided liver biopsy for the diagnosis of chronic liver disease (CLD). We aimed to evaluate the correlation between PPG and clinical markers of PH, and assess the feasibility and safety of concomitant, single session EUS‐PPG and EUS‐bx. Methods: This was a retrospective study of patients undergoing EUS‐PPG for CLD at a single tertiary endoscopy center between February 2014 and March 2020. EUS‐PPG was performed using a 25‐gauge needle and compact manometer. Data analysis was performed with SAS version 9.4. Results: Eighty‐three patients underwent EUS‐PPG with 100% technical success. The mean PPG was 7.06 mmHg (SD 6.09, range 0–27.3). PPG was higher in patients with ( vs without) clinical features of cirrhosis (9.46 vs 3.61 mmHg, P < 0.0001), esophageal or gastric varices (13.88 vs 4.34 mmHg, P < 0.0001), and thrombocytopenia (9.25 vs 4.71 mmHg, P = 0.0022). In the 71 patients (85.5%) who underwent EUS‐bx, 70 (98.6%) specimens were deemed adequate by the pathologist for histologic diagnosis. There were no early or late major adverse events. Conclusion: EUS‐PPG correlates well with clinical markers of PH. EUS‐bx can be performed safely during the same session as EUS‐PPG, providing a comprehensive endoscopic evaluation of the patient with CLD.